Radiation-Induced Hemorrhagic Cystitis in Prostate Cancer Survivors: The Hidden Toll - René Gatsinga; Benjamin J. H. Lim; Navin Kumar; Jacinda G. G. Tan; Youquan Li; Michael L. C. Wang; Terence W. K. Tan; Jeffrey K. L. Tuan; Yu Guang Tan; Kenneth Chen; John S. P. Yuen (Medicina)
Background and Objectives: Radiation therapy (RT) plays a crucial role in managing prostate cancer, offering effective disease control and improving survival rates in both localized and recurrent cases. However, RT can lead to hemorrhagic cystitis, a significant late complication resulting in chronic morbidity and other health issues. This study aims to evaluate the real-world incidence of radiation-induced hemorrhagic cystitis requiring surgical intervention. Materials and Methods: This retrospective cohort study analyzed data from prostate cancer survivors treated for hematuria at our center between January 2014 and January 2024. Patients were included if cystoscopy identified radiation cystitis as the cause of hematuria. Descriptive statistics were used, and binomial logistic regression analyses with univariate and multivariate analysis were performed to identify risk factors for worse outcomes. Results: Fifty-two patients met the inclusion criteria. The estimated cumulative incidence at a median follow-up of 5.3 years was 4.5%. Among the participants, 21.2% required more than two transurethral bladder fulguration (TUBF) procedures, and 38.5% needed more than two hospital admissions for hematuria management. The median time to the first fulguration was 64 months. Blood transfusions were necessary in 53.8% of cases, and 38.5% required hyperbaric oxygen therapy. Ultimately, 5.8% of the patients underwent cystectomy. Univariate analysis identified ischemic heart disease (IHD) and antiplatelet therapy as significant risk factors (OR: 5.17 and 5.18, respectively), along with longer time to first fulguration (OR: 5.02). Multivariate analysis confirmed antiplatelet therapy (OR: 2.8, p = 0.05) and time to first TUBF (OR: 1.8, p = 0.02) as significant predictors of multiple procedures. Conclusions: Radiation cystitis remains a significant burden on prostate cancer survivors. Patients on antithrombotic agents, those with delayed initial presentations, and those who received radiation as salvage therapy are more likely to experience higher morbidity.